A study on facilities and level of service provided by KSM for a long distance express bus service / Marziana Khalid - Khalid, Marziana (1993)
This thesis,therefore was undertaken to develop the steps to be taken to fulfill the requirement of customer needs include level of service and facilities provided, which is one of the most significant aspect that need a study. The first chapter of this thesis will highlight on the back ground of the study, objectives, the problem statement, scope and limitation and also the methodology that will be used throughout this thesis. In the second chapter, will be explain the customer needs for facilities as well as level of service. In this chapter, all of the data is a secondary data such as library books and magazines. Chapter three of this thesis is about the critique of Kenderaan Sungai Manik, about the facilities and level of service that provided by this company. It will shown the good and bad side of the operation including the facilities and level of service provided by Kenderaan Sungai Manik Sdn Bhd Chapter four of this thesis will be discussing the findings of the research. It will cover both primary and secondary research instruments. Besides that, the findings of the questionaires will also be presented. The findings of the customer needs on the Teluk Intan to Singapore , the long distance express bus service will be analysed in this chapter. Finally, in the last chapter, he recommendation and conclusion will be presented. Several fine suggestion will recommend to the company regarding the study and eventually will conclude this thesis.